2010
DOI: 10.4161/auto.6.4.11819
|View full text |Cite
|
Sign up to set email alerts
|

GABARAPL1 (GEC1) associates with autophagic vesicles

Abstract: Gabarapl1 (gec1) was first described as an estrogen regulated gene which shares a high sequence homology with the gabarap gene. We previously demonstrated that GABARAPL1, like GABARAP, interacts with the GABAA receptor and tubulin and promotes tubulin polymerization. Previous work has demonstrated that the GABARAP family members (GABARAP, LC3, GATE-16 and Atg8) are not only involved in the transport of proteins or vesicles but are also implicated in various mechanisms such as autophagy, cell death, cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 45 publications
7
85
1
1
Order By: Relevance
“…1). 11,12 In addition to their sequence similarity, the crystal structures of GABARAP, [13][14][15][16][17] GATE-16, 6 LC3, 18 and…”
Section: The Gabarap Familymentioning
confidence: 99%
See 2 more Smart Citations
“…1). 11,12 In addition to their sequence similarity, the crystal structures of GABARAP, [13][14][15][16][17] GATE-16, 6 LC3, 18 and…”
Section: The Gabarap Familymentioning
confidence: 99%
“…These studies have shown that the cellular distribution of GABARAPL1 is highly variable, including the cytoplasm, Golgi complex, endoplasmic reticulum or the plasma membrane, but with a common feature, a staining linked to intracytoplasmic vesicles that can partially colocalize with autophagosomes or lysosomes. 45,46,48,49 Although these experiments make it possible to determine the expression pattern of exogenous GABARAPL1, the cellular distribution of endogenous GABARAPL1 remains to be confirmed.…”
Section: The Role Of Gabarapl1 In Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…2B, lane 3), producing only one signal corresponding to the with a higher percentage of acrylamide in the gel and a longer migration time. 3,13 Immunohistological analysis of the endogenous proteins, however, does not provide an easy alternative to the necessity of specific antibodies. Indeed, many researchers have encountered this problem of cross-reactivity with both their 'homemade' and commercially bought antisera and purified antibodies raised against either GABARAPL1 or GABARAP.…”
Section: Gabarapl1 (Gec1) Antibodiesmentioning
confidence: 99%
“…3 The exact role of GABARAPL1 in intracellular transport and autophagy, however, is still unanswered, and will require further studies to address the remaining uncertainties. As with any experiment, the proper tools are critical to its success.…”
Section: Introductionmentioning
confidence: 99%